Mapping Ability Literacy Science School Base Class V on Material Temperature and Heat - Maulana, Rindu; Wati, Risna; Vebrianto, Rian; Hamdani, M. Fikri; Yuliastrin, Adisti (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine: (1) the profile and science literacy skills of fifth grade elementary school students and (2) differences in science literacy skills based on age, ethnicity, gender, parental education and parental occupation. This study used a survey method with a quantitative approach, with a total sample of 60 people taken through purposive sampling technique. All data were collected through test questions distributed online and analyzed quantitatively using the IBM SPSS 24 application and the Two - way ANOVA test. The results showed that: (1) aspects of science literacy skills have an average of 77 with a good category, (2) There are no differences in science literacy skills based on age, gender, parental occupation and parental education.